Assessing Undergraduate University Students' Level of Knowledge, Attitudes and Behaviour Towards Biodiversity: A case study in Cyprus - Nisiforou, Olympia A.; Charalambides, Alexandros G. (My University, 2012)
Biodiversity is a key resource as it provides both goods and services to society. However, humans value these resources differently, especially when biodiversity is exploited for its economic potential; a destruction on a scale rarely seen before. In order to decrease the threats that biodiversity is facing due to human activity, globally (climate change) and locally (economic development), individuals must have fundamental knowledge and exhibit appropriate behaviour towards biodiversity and its values. Nevertheless, the effect of human's knowledge, policies and attitudes towards biodiversity's protection are often limited by insufficient education and public support. A balance between the use of resources and technology, reconciling economic development and the need to maintain biodiversity is a challenge. The current paper looks into the knowledge level, attitudes and behaviour of university students of the Department of Environmental Science and Technology at the Cyprus University of Technology towards biodiversity. The investigation was carried out using a closed format questionnaire on a sample of first- and second-year university students (n = 44), in order to access their perceptions and attitudes towards environmental issues regarding biodiversity. The questionnaire was derived from relevant literature. The test results showed that there are significant differences with regard to the level of knowledge about biodiversity between the two groups. However, no significant differences were found on attitudes and behaviour towards biodiversity. The results have also shown that all students have a positive attitude towards biodiversity, while on the other hand, they find themselves, most of the time, unwilling to engage in environmental behaviour.
Keywords: Environmental education; Biodiversity loss; Attitudes; Knowledge; Behaviour